Fine Tuning of Phosphorothioate Inclusion in 2′-O-Methyl Oligonucleotides Contributes to Specific Cell Targeting for Splice-Switching Modulation - Aoki, Yoshitsugu; Rocha, Cristina S. J.; Lehto, Taavi; Miyatake, Shouta; Johansson, Henrik; Hashimoto, Yasumasa; Nordin, Joel Z.; Mager, Imre; Aoki, Misako; Graham, McClorey; Sathyaprakash, Chaitra; Roberts, Thomas C.; et al. (Frontiers in Physiology, 2021)
Splice-switching antisense oligonucleotide- (SSO-) mediated correction of framedisrupting mutation-containing premessenger RNA (mRNA) transcripts using exon skipping is a highly promising treatment method for muscular diseases such as Duchenne muscular dystrophy (DMD). Phosphorothioate (PS) chemistry, a commonly used oligonucleotide modification, has been shown to increase the stability of and improve the pharmacokinetics of SSOs. However, the effect of PS inclusion in 2′-O-methyl SSOs (2OMe) on cellular uptake and splice switching is less well-understood. At present, we demonstrate that the modification of PS facilitates the uptake of 2OMe in H2k-mdx myoblasts. Furthermore, we found a dependency of SSO nuclear accumulation and high splice-switching activity on PS inclusion in 2OMe (2OMePS), as tested in various reporter cell lines carrying pLuc/705. Increased exon-inclusion activity was observed in muscle, neuronal, liver, and bone cell lineages via both the gymnotic uptake and lipofection of 2OMePS. Using the photoactivatable ribonucleoside-enhanced crosslinking and a subsequent proteomic approach, we identified several 2OMePS-binding proteins, which are likely to play a role in the trafficking of 2OMePS to the nucleus. Ablation of one of them, Ncl by small-interfering RNA (siRNA) enhanced 2OMePS uptake in C2C12 myoblasts and upregulated luciferase RNA splicing in the HeLa Luc/705 reporter cell line. Overall, we demonstrate that PS inclusion increases nuclear delivery and splice switching in muscle, neuronal, liver, and bone cell lineages and that the modulation of 2OMePS-binding partners may improve SSO delivery.